2015
DOI: 10.1371/journal.pone.0116649
|View full text |Cite
|
Sign up to set email alerts
|

Goat Uterine DBA+ Leukocytes Differentiation and Cytokines Expression Respond Differently to Cloned versus Fertilized Embryos

Abstract: High rate of fetal mortality in ruminant somatic cell nuclear transfer (SCNT) pregnancies is due, at least in part, to immune-mediated abortion of fetuses. In the present study, goat uterine leukocytes were isolated by Dolichos biflorus agglutinin (DBA) coated magnetic beads, and with majority being were CD56+CD16- in phenotype with low levels of perforin and Granzyme B expression. The responses of the isolated cells to SCNT and in vitro fertilization (IVF) embryos conditioned mediums containing hormone steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Interferon-γ is primarily produced by NK cells and play a role in shaping the T-helper 1 (Th1) immune responses. Previous work from our laboratory showed that TWEAK decreases the expression of IFN-γ and the cytotoxicity of goat uterine NK cells, a major lymphocyte population in the endometrium of goat (47,48). Here, our data also support a negative role of TWEAK in regulating peripheral NK cell IFN-γ production.…”
Section: Discussionsupporting
confidence: 86%
“…Interferon-γ is primarily produced by NK cells and play a role in shaping the T-helper 1 (Th1) immune responses. Previous work from our laboratory showed that TWEAK decreases the expression of IFN-γ and the cytotoxicity of goat uterine NK cells, a major lymphocyte population in the endometrium of goat (47,48). Here, our data also support a negative role of TWEAK in regulating peripheral NK cell IFN-γ production.…”
Section: Discussionsupporting
confidence: 86%
“… B.suis.S2 infection disturbed PR and EαR protein expression under progesterone stimulation in EECs . Caprine endometrial epithelial cells (EECs) were cultured with complete DMEM/F12 medium containing P4 (10 −7 M, Sigma-Aldrich; Qin et al, 2015 ). B.suis.S2 infection assays were performed as described in the Materials and Methods.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Many previous in vitro studies used hormones to mimic the uterine environment during early pregnancy (Qi et al, 2012;Qin et al, 2015). In our research, we measured the expression of COPS5 in goat EECs under P 4 , E 2 , and IFNT treatments.…”
Section: Expression Of Cops5 In Eecs Under Hormone Treatmentmentioning
confidence: 99%